2021
DOI: 10.3389/fcell.2021.635263
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Biomechanics of Leukocyte Transendothelial Migration by Quantitative Imaging

Abstract: Leukocyte transendothelial migration is crucial for innate immunity and inflammation. Upon tissue damage or infection, leukocytes exit blood vessels by adhering to and probing vascular endothelial cells (VECs), breaching endothelial cell-cell junctions, and transmigrating across the endothelium. Transendothelial migration is a critical rate-limiting step in this process. Thus, leukocytes must quickly identify the most efficient route through VEC monolayers to facilitate a prompt innate immune response. Biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 135 publications
(222 reference statements)
0
14
0
Order By: Relevance
“…In our experiments, the activated endothelial cells themselves were the source of the CCR2 ligands mediating TEM, thereby obviating a requirement for ACKR1 in endothelial cell transport and/or presentation, and we found no evidence of CCR2 ligands localized at endothelial cell junctions. Nonetheless, it is possible that chemokine secreted on the abluminal side could be presented at the junctions by endothelial cell ACKR1 and form a gradient sensed by the leukocytes’ invading podosomes 97 . In this regard, both CCL2 and CCL7 bind well to ACKR1 98 .…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, the activated endothelial cells themselves were the source of the CCR2 ligands mediating TEM, thereby obviating a requirement for ACKR1 in endothelial cell transport and/or presentation, and we found no evidence of CCR2 ligands localized at endothelial cell junctions. Nonetheless, it is possible that chemokine secreted on the abluminal side could be presented at the junctions by endothelial cell ACKR1 and form a gradient sensed by the leukocytes’ invading podosomes 97 . In this regard, both CCL2 and CCL7 bind well to ACKR1 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is tightly regulated and is associated with the transient crossing of leukocytes through the blood vessel wall, a process called transendothelial migration (TEM) 37 . The scope and speed of the innate immune response is primarily dictated by TEM 38 . It is interesting that TEM had been activated in the mobilization of leucocytes from spleen to other tissues in the adjuvanted animals, but not in the vaccinated animals, so we can hypothesize that different cellular migrations occur depending on the inoculated molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The role of force-dependent integrin binding in cell-cell adhesion and cell-ECM interaction is indispensable. Different force-based imaging techniques have observed the biomechanics of leukocyte circulation, endothelial and transendothelial migration, and their persistence in the surrounding matrix (Schwartz et al, 2021). For example, traction force microscopy (TFM) has revealed that neutrophils and migrating T cells have force exertion concentrated in the rear side, where fully activated extended integrins are also found to cluster, similar to a "rear-wheel drive" mechanism (Jannat et al, 2011a;Dixit et al, 2011;Smith et al, 2007;Green et al, 2006).…”
Section: Integrin-talin Centered Focal Adhesionmentioning
confidence: 99%